Autologous micro-fragmented adipose tissue associated with arthroscopy in moderate–severe knee osteoarthritis: outcome at two year follow-up - Andrea Giorgini; Filippo Selleri; Francesco Zambianchi; Giacomo Cataldo; Elena Francioni; Fabio Catani (BMC Musculoskeletal Disorders, 2022)
Abstract Background Adipose tissue has recently gained growing interest in the treatment of osteoarthritis (OA). The aim of the present study was to evaluate the efficacy of a single injection of autologous micro-fragmented adipose tissue (aMFAT) associated with arthroscopy (cartilage debridement/meniscal regularization or selective meniscectomy/micro-drilling) for symptomatic knee OA. Methods This retrospective, single-center study included 49 patients (50 knees) affected by knee OA (radiographic Kellgren-Lawrence III-IV) treated with a single injection of autologous micro-fragmented adipose tissue and knee arthroscopy. Knee Injury and Osteoarthritis Outcome Score (KOOS) and subjective International Knee Documentation Committee (IKDC) score were the primary outcome measures and were collected at one and 2 years post-operatively. Patients were divided into clusters based on age, complexity of arthroscopic procedures and chondral lesion grade. Results Four patients underwent knee replacement (8%). No major adverse events were reported. Minimal Clinically Important Difference (MCID) for KOOS and IKDC was reached by 84 and 74% of all cases at 1 year and by 80 and 76% at 2 years, respectively. High grade chondral lesions negatively affected the outcome at 2 years follow-up (p < 0.05 for IKDC, KOOS overall and 3 out of 5 subscales). Conclusion The injection of micro-fragmented adipose tissue associated with arthroscopy demonstrated to be a safe and effective procedure for the treatment of knee OA, with a substantial improvement in IKDC and KOOS scores and without major complications.